Pengaturan Corporate Social Responsibility (CSR) di Indonesia (Lex Jurnalica, 2010)
Corporate Social Responsibility (CSR) or environmental responsibility is in fact the responsibility of every legal person, including corporations. In the event of environmental damage in the operations of the company, then it will go to the jurisdiction. The development of CSR in Indonesia and has been widely implemented five years. CSR applied to activities that touch the social aspects, education, skills training and economic aspects. Settings CSR in Indonesia is expressly provided for in Law no. 25 of 2007 on Investment, Law no. 40 Year 2007 regarding Limited Liability Companies, and Law no. 23 of 1997 on Environmental Management. Writing method used is the juridical normative, while the techniques of collecting data obtained from the research literatureÂ Keywords: Regulating, Corporate Social Responsibility, IndonesiaÂ